Disease-Related Protein Variants of the Highly Conserved Enzyme PAPSS2 Show Marginal Stability and Aggregation in Cells - Brylski, Oliver; Shrestha, Puja; House, Philip J.; Gnutt, Patricia; Mueller, Jonathan Wolf; Ebbinghaus, Simon (Frontiers in Molecular Biosciences, 2022)
Cellular sulfation pathways rely on the activated sulfate 3'-phosphoadenosine-5'-phosphosulfate (PAPS). In humans, PAPS is exclusively provided by the two PAPS synthases, PAPSS1 and PAPSS2. Mutations found in the PAPSS2 gene result in severe disease states such as bone dysplasia, androgen excess and polycystic ovary syndrome. The APS kinase domain of PAPSS2 catalyzes the rate-limiting step in PAPS biosynthesis. In this study, we show that clinically described disease mutations located in the naturally fragile APS kinase domain are associated either with its destabilization and aggregation or its deactivation. Our findings provide novel insights into possible molecular mechanisms that could give rise to disease phenotypes associated with sulfation pathway genes.